5 - Researching Radio Audiences in an Emerging Pluralistic Media Environment: A Case for the Focus Group Discussion (FGD) Method - Margaret I. Amoakohene, (Africa Media Review, 2004)
The central thesis of this article is that the focus group discussion method of the qualitative research methodology has huge and largely unexploited potentials for use as a tool for audience research in a new democracy with a newly liberate media environment. It argues that the use of the method by Paul Lazarsfeld, Robert Merton and their colleagues at the Bureau of Applied Social Research at Columbia University to gauge audience responses and reactions to propaganda and radio broadcasts set the pace for its use in audience research. Through extensive use in, and adaptations to, different research environments, focus groups have demonstrated an ability to function as fully-fledged methods of data collection. The article examines literature on the history, development, and use of focus groups in many fields of study including media and communication to show that the method has advantages for audience research in a competitive media market. Through this perspective, and with reference to a number of studies carried out by the author in Ghana using this method, it recognises focus group research as an appropriate method for researching media, especially radio, audiences and recommends it to media owners.